Chemical composition and antioxidant activity of Alphonsea monogyna - Nguyen , Dinh Quynh Phu; Nguyen , Thi Sen; Hoang , Xuan Huyen Trang; Nguyen , Khanh Thuy Linh; Doan , Quoc Tuan (Tạp chí Y Dược Huế, 2025)
Background: Alphonsea monogyna has been recorded in Vietnam and studied for its alkaloid constituents, essential oil composition and antibacterial activity. However, there is limited research on its other chemical constituents and antioxidant properties. This study aimed to determine the total phenolic, total flavonoid and total alkaloid contents, along with antioxidant activity of A. monogyna. Materials and methods: Whole plants of A. monogyna were collected in Hue City. The total phenolic and total flavonoid contents were determined using the Folin-Ciocalteu and AlCl3 methods, respectively. The total alkaloid content was determined by the gravimetric method. 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) assays were used to evaluate antioxidant activity. Results: The ethanol extract from the branches of A. monogyna exhibited a notable total phenolic content of 102.68 ± 1.25 mg GAE/g extract. The flavonoid content was found to be 2.13 ± 0.06 mg QE/g extract in the leaves and 1.29 ± 0.04 mg QE/g extract in the branches. The total alkaloid content in the leaves and branches of A. monogyna was 0.70 ± 0.02% and 0.28 ± 0.02%, respectively. In both DPPH and ABTS assays, the branch extract showed stronger antioxidant activity than the leaf extract, with IC50 values of 45.62 ± 0.64 μg/mL and 8.37 ± 0.28 μg/mL, respectively. In comparison, the positive control, ascorbic acid, demonstrated significantly lower IC50 values of 2.69 ± 0.09 μg/mL for DPPH and 1.27 ± 0.08 μg/mL for ABTS. Conclusion: This study provided valuable insights into the chemical composition of Alphonsea monogyna, detailing the total phenolic, flavonoid, and alkaloid contents, as well as its antioxidant activity.